Talazoparib plus enzalutamide in men with metastatic castration-resistant prostate cancer: final overall survival results from the randomised, placebo-controlled, phase 3 TALAPRO-2 trial - Agarwal, Neeraj; Azad, Arun A; Carles, Joan; Fay, André P; Matsubara, Nobuaki; Szczylik, Cezary; De Giorgi, Ugo; Young Joung, Jae; Fong, Peter C C; Voog, Eric; Jones, Robert J; Shore, Neal D; et al. (The lancet, 2025)
Background - The primary analysis of this phase 3 trial combining talazoparib with enzalutamide demonstrated significantly improved radiographic progression-free survival (rPFS) versus enzalutamide plus placebo in patients with metastatic castration-resistant prostate cancer unselected for homologous recombination repair (HRR) gene alterations. Overall survival data were immature at that time. Here we report the final prespecified overall survival analysis, an updated descriptive analysis of rPFS, and safety in the cohort unselected for HRR gene alterations. - Methods - TALAPRO-2 was a randomised, double-blind, placebo-controlled, phase 3 trial. In the genetically unselected cohort, patients were randomly assigned from 200 centres, including hospitals, cancer centres, and medical centres, in 26 countries in North America, Europe, Israel, South America, South Africa, and the Asia-Pacific region. Adult men (aged ≥18 years [≥20 years in Japan]) with asymptomatic or mildly symptomatic metastatic castration-resistant prostate cancer receiving ongoing androgen deprivation therapy, and with no previous life-prolonging systemic therapy for castration-resistant prostate cancer, were randomly assigned (1:1) to talazoparib 0·5 mg plus enzalutamide 160 mg or enzalutamide plus placebo, administered orally once daily as initial treatment for metastatic castration-resistant prostate cancer, stratified by HRR gene alteration status (HRR-deficient vs HRR-non-deficient or unknown) and previous treatment for castration-sensitive disease (yes vs no). The sponsor, patients, and investigators were masked to talazoparib or placebo, and enzalutamide was open label. The primary endpoint was rPFS by blinded independent central review, and overall survival (time from randomisation to death due to any cause) was an event-based α-protected key secondary endpoint (α-threshold at final overall survival analysis was 0·022 [two-sided])—both assessed in the intention-to-treat population. Follow-up for overall survival was intended to continue until the planned final analysis. Safety was assessed in patients who received at least one dose of a study drug. This study is registered with ClinicalTrials.gov, NCT03395197, and is ongoing. - Findings - Between Jan 7, 2019, and Sept 17, 2020, 993 patients were assessed for eligibility, of whom 188 (19%) patients were excluded and 805 (81%) patients were enrolled and randomly assigned (402 [50%] to talazoparib plus enzalutamide, 403 [50%] to enzalutamide plus placebo). At a median follow-up of 52·5 months (IQR 48·6-56·0), overall survival was significantly improved with talazoparib plus enzalutamide compared with enzalutamide plus placebo (hazard ratio [HR] 0·80 [95% CI 0·66-0·96]; p=0·016); median overall survival was 45·8 months (95% CI 39·4-50·8) in the talazoparib group compared with 37·0 months (34·1-40·4) in the control group. Overall survival favoured talazoparib plus enzalutamide over enzalutamide plus placebo in HRR-deficient patients (n=169; HR 0·55 [0·36-0·83]; p=0·0035) and to a lesser extent in HRR-non-deficient or unknown patients (n=636; HR 0·88 [0·71-1·08]; p=0·22). Updated rPFS also favoured talazoparib plus enzalutamide (HR 0·67 [0·55-0·81]; p<0·0001); median rPFS was 33·1 months for talazoparib plus enzalutamide versus 19·5 months for enzalutamide plus placebo. Safety was consistent with the known profile of talazoparib; common grade 3 or higher adverse events with talazoparib plus enzalutamide were anaemia (195 [49%] vs 18 [4%] patients with enzalutamide plus placebo) and neutropenia (77 [19%] vs six [1%] patients with enzalutamide plus placebo). - Interpretation - Combining talazoparib with enzalutamide significantly improved overall survival in patients with metastatic castration-resistant prostate cancer, supporting this combination as a standard-of-care initial treatment option for these patients. - Funding - Pfizer.